Intergenerational Transmission of Emotion Dysregulation Through Parental Invalidation of Emotions: Implications for Adolescent Internalizing and Externalizing Behaviors - Buckholdt, Kelly E. (2013)
We examined parent emotion dysregulation as part of a model of family emotion-related processes and adolescent psychopathology. Participants were 80 parent–adolescent dyads (mean age = 13.6; 79 % African-American and 17 % Caucasian) with diverse family composition and socioeconomic status. Parent and adolescent dyads self-reported on their emotion regulation difficulties and adolescents reported on their perceptions of parent invalidation (i.e., punishment and neglect) of emotions and their own internalizing and externalizing behaviors. Results showed that parents who reported higher levels of emotion dysregulation tended to invalidate their adolescent’s emotional expressions more often, which in turn related to higher levels of adolescent emotion dysregulation. Additionally, adolescent-reported emotion dysregulation mediated the relation between parent invalidation of emotions and adolescent internalizing and externalizing behaviors. Potential applied implications are discussed.